Pengembangan Lembar Kerja Peserta Didik Berbasis STEM pada Materi Transformasi Geometri di Kelas XI SMA - Syamsiah Rohmah Ama; Syutaridho Syutaridho; Ambarsari Kusuma Wardani (JEMST (Jurnal of Education in Mathematics, Science, and Technology), 2023)
This study aims to obtain STEM-based LKPD for the EDP learning model developed for Geometry Transformation material, to determine the feasibility of LKPD, to find out students' responses to LKPD, and to find out the potential effect on students' creative thinking after using the LKPD. The subjects of this study were 3 teachers as material experts, 2 lecturers and 1 design expert teacher, as well as 25 class XI students of SMA IBA Palembang for the 2022/2023 academic year. The level of feasibility is seen from the results of the assessment of material experts and design experts. Meanwhile, students' responses were seen from the results of the questionnaire after using the STEM-based LKPD that had been developed. This study uses the ADDIE research model (Analysis, Design, Develop, Implement, Evaluation). Based on the results of the experts' assessment, it was obtained STEM-based LKPD that was feasible to apply to the Geometry Transformation subject. Student responses were obtained by 86,6% in the practical category. As for students' creative thinking skills, it was obtained that 84% of students completed the creative thinking test. The conclusion obtained from this study is that STEM-based LKPD on Geometry Transformation material is very suitable for use as teaching material. Keywords : LKPD, STEM, Geometry Transformation, Creative Thinking